Axial-Bonding-Driven Dimensionality Effect on the Charge-Density Wave in NbSe2 - Lin, Dongjing; Ranjbar, Ahmad; Li, Xiaoxia; Huang, Xinyu; Huang, Yuan; Berger, Helmuth; Forro, Laszlo; Watanabe, Kenji; Taniguchi, Takashi; Belosludov, Rodion V.; Kühne, Thomas D.; Ding, Haifeng; et al. (Nano Letters, 2022)
2H-NbSe2is a prototypical charge-density-wave (CDW) system, exhibiting such a symmetry-breaking quantum ground state in its bulk and down to a single-atomic-layer limit. However, how this state depends on dimensionality and what governs the dimensionality effect remain controversial. Here, we experimentally demonstrate a robust 3 × 3 CDW phase in both freestanding and substrate-supported bilayer NbSe2, far above the bulk transition temperature. We exclude environmental effects and reveal a strong temperature and thickness dependence of Raman intensity from an axially vibrating A1gphonon mode, involving Se ions. Using first-principles calculations, we show that these result from a delicate but profound competition between the intra- and interlayer bonding formed between Se-pzorbitals. Our results suggest the crucial role of Se out-of-plane displacement in driving the CDW distortion, revealing the Se-dominated dimensionality effect and establishing a new perspective on the chemical bonding and mechanical stability in layered CDW materials.
CRIS-Team Scopus Importer:2023-03-20
Keywords: charge-density waves; chemical bonding; first-principles calculations; Raman spectroscopy